2020
DOI: 10.5194/acp-20-8441-2020
|View full text |Cite
|
Sign up to set email alerts
|

Adding value to extended-range forecasts in northern Europe by statistical post-processing using stratospheric observations

Abstract: Abstract. The strength of the stratospheric polar vortex influences the surface weather in the Northern Hemisphere in winter; a weaker (stronger) than average stratospheric polar vortex is connected to negative (positive) Arctic Oscillation (AO) and colder (warmer) than average surface temperatures in northern Europe within weeks or months. This holds the potential for forecasting in that timescale. We investigate here if the strength of the stratospheric polar vortex at the start of the forecast could be used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Our results are comparable to those of Lynch et al (2014), who concluded that there is statistically significant skill in predicting weekly mean wind speeds over areas of Europe at lead times of at least 14-20 d. Lynch et al (2014) used five years of operational forecasts; their CIs were narrower than ours, and they could make better inference using operational forecasts.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our results are comparable to those of Lynch et al (2014), who concluded that there is statistically significant skill in predicting weekly mean wind speeds over areas of Europe at lead times of at least 14-20 d. Lynch et al (2014) used five years of operational forecasts; their CIs were narrower than ours, and they could make better inference using operational forecasts.…”
Section: Discussionsupporting
confidence: 84%
“…Including such information in NGR is rather straight-forward. Furthermore, the most advanced non-linear methods (such as deep learning, e.g., Liu et al, 2016) need a large amount of training data to avoid overfitting, and the data sets available in subseasonal forecasting are of relatively modest size. Therefore, NGR, trainable with reasonable small data, is a feasible choice for future applications.…”
Section: Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the observational coverage of these two layers is nowhere near as dense as that of the troposphere. Some of the largest uncertainties in current reanalyses occur in these levels, leading the wind representation of mesospheric winds to lag behind other areas (Baker et al ., 2014; Korhonen et al ., 2019). For instance, Duruisseau et al .…”
Section: Introductionmentioning
confidence: 99%